2010
DOI: 10.1103/physreva.82.042717
|View full text |Cite
|
Sign up to set email alerts
|

Low-energy inelastic collisions of OH radicals with He atoms andD2molecules

Abstract: We present an experimental study on the rotational inelastic scattering of OH (X 2 3/2 ,J = 3/2,f ) radicals with He and D 2 at collision energies between 100 and 500 cm −1 in a crossed beam experiment. The OH radicals are state selected and velocity tuned using a Stark decelerator. Relative parity-resolved state-to-state inelastic scattering cross sections are accurately determined. These experiments complement recent low-energy collision studies between trapped OH radicals and beams of He and D 2 that are se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 46 publications
3
56
0
Order By: Relevance
“…Recently, we have studied the low-energy state-to-state rotationally inelastic scattering cross sections for this system by scattering a beam of Stark-decelerated OH radicals with a conventional beam of He atoms in a crossed molecular beam (90 degrees crossing angle) configuration. 34 In this experiment, the velocity of the He atoms is B1000 m s À1 , and the collision energy is tuned by varying the OH velocity using the Stark decelerator. In panel (a) of Fig.…”
Section: Resonances In Oh-he Collisionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we have studied the low-energy state-to-state rotationally inelastic scattering cross sections for this system by scattering a beam of Stark-decelerated OH radicals with a conventional beam of He atoms in a crossed molecular beam (90 degrees crossing angle) configuration. 34 In this experiment, the velocity of the He atoms is B1000 m s À1 , and the collision energy is tuned by varying the OH velocity using the Stark decelerator. In panel (a) of Fig.…”
Section: Resonances In Oh-he Collisionsmentioning
confidence: 99%
“…10 The tunability of the velocity allows for scanning of the collision energy in a fixed experimental geometry. State-to-state inelastic scattering between Stark-decelerated OH radicals and conventional beams of Xe, Ar, and He atoms, as well as D 2 molecules, [11][12][13] has been studied. These beam deceleration methods hold great promise for future scattering experiments and offer the possibility to extend the available collision energy range to energies below one wavenumber.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the velocity spread in such decelerated beams is much smaller than in conventional molecular beams. Thus far, an energy resolution of ≥ 13 cm −1 has been achieved for collisions of OH radicals with rare gas atoms [13][14][15]. This resolution is mainly limited by the velocity and angular spread of the atomic collision partner, and is too low to experimentally resolve scattering resonances.…”
Section: Introductionmentioning
confidence: 99%
“…Early calculations [17,18] on rotationally inelastic scattering of N 2 molecules with He atoms have shown that resonances occur at low collision energies, but the experimental verification of these predictions was not yet possible. Collisions of OH(X 2 Π) with rare gases have emerged as paradigms of scattering of an open-shell molecule with an atom [13,15,[19][20][21][22][23][24]. The OH-rare gas systems are good candidates for the observation and analysis of resonances in rotationally inelastic collisions because the collision energy can be reduced by Stark deceleration of the OH beam.…”
Section: Introductionmentioning
confidence: 99%
“…6 This body of work extended the scope of inelastic scattering of labile free radicals, which had previously concentrated on collisions of diatomic radicals with atomic species. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] A recent article by Dagdigian reviewed collisional energy transfer calculations for small hydrocarbon intermediates 26 and highlighted computational studies of integral cross sections for collisions of methylene (CH 2 ) 27,28 and methyl radicals. 5,28,29 The methyl radical is also the first polyatomic free radical to be slowed in a Zeeman decelerator using a pulsed magnetic field, 30 opening up new possibilities to study inelastic and reactive scattering at very low collision energies.…”
Section: Introductionmentioning
confidence: 99%